Development of local wisdom-based ecotourism traditional houses in the digital age - I Ketut Sarka; Phung Thi Thao (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: In the post-pandemic era, Bali’s tourism industry has shifted toward natural attractions to avoid mass tourism. In Sembung Village, Badung, the development of ecotourism rooted in tradition and culture is now integrated with digital technology. This study aims to analyze the development of ecotourism in the region while preserving the philosophical values of traditional Balinese houses from excessive commodification. Methods: This study uses a qualitative research approach to understand why and how the potential of traditional Balinese houses can be developed into a sustainable ecotourism model. Findings: The development of traditional house-based ecotourism in Sembung Village in the digital era is at the crossroads of conservation through commercialization and authenticity versus modernization. Conclusion: The key differentiator (strategic strength) of Sembung Village lies in the philosophical authenticity of its traditional houses, which modern resorts cannot replicate. The development strategy should focus on Digital Narrative-Based Marketing that uses in-depth storytelling to attract the sustainable tourism market segment that values ethics and education. Technology becomes a bridge to narrate philosophy, not just a tool for mass promotion. The most appropriate sustainable tourism model is the Education-Homestay model, managed through the Village-Owned Enterprise (BUMDes). Novelty/Originality of this article: This research bridges the research gap by offering a development model in Sembung Village, where digital technology is not only used for promotion but also as an educational tool to preserve the philosophy of traditional houses.